Thinking and deciding - Baron, Jonathan, 1944- (Cambridge University Press, 2008)
Beginning with its first edition and through subsequent editions, Thinking and Deciding has established itself as the required text and important reference work for students and scholars of human cognition and rationality. In this fourth edition, first published in 2007, Jonathan Baron retains the comprehensive attention to the key questions addressed in the previous editions - how should we think? What, if anything, keeps us from thinking that way? How can we improve our thinking and decision making? - and his expanded treatment of topics such as risk, utilitarianism, Baye's theorem, and moral thinking. With the student in mind, the fourth edition emphasises the development of an understanding of the fundamental concepts in judgement and decision making. This book is essential reading for students and scholars in judgement and decision making and related fields, including psychology, economics, law, medicine, and business.